Anthropometrical parameters and markers of obesity in rats - Novelli, E. L. B.; Diniz, Y. S.; Galhardi, C. M.; Ebaid, G. M. X.; Rodrigues, H. G.; Mani, F.; Fernandes, Ana Angelica Henrique [UNESP]; Cicogna, Antonio Carlos [UNESP]; Novelli, J. L. V. B. (Royal Soc Medicine Press Ltd, 2007)
The present study was undertaken to determine anthropometrical parameters in male adult Wistar rats. We tested the hypothesis that the anthropometrical index may identify obesity and may predict its adverse effects on lipid profile and oxidative stress in rats. Two experimental protocols were performed. in the first experiment, 50 male Wistar rats, 21 days old and fed a control chow were studied up to 150 days of age. in the second experiment, male Wistar rats, 60 days old, were divided into three groups (n = 8): control (C) given free access to a control chow; (S) receiving the control chow and drinking 30% sucrose ad libitum and (HQ fed a high-carbohydrate diet ad libitum. The first experiment showed that food consumption, energy intake and body weight increased with increasing age, while specific rate of body mass gain was significantly decreased. There were no significant differences in body length and thoracic circumference of rats from 60 days of age. The abdominal circumference (AC) and body mass index (BMI) significantly increased with enhancing age in rats up to 90 days of age and remained constant thereafter. In the second experiment, after 30 days of dietary treatment, the final body weight, body mass gain, carcass fat and BMI were higher in S and HC rats than in C. There were no significant alterations in body length and carcass protein among the groups. Triacylglycerol (TG), total cholesterol (CT), low-density lipoprotein cholesterol (LDL-C) and lipid hydroperoxide (LH) were higher in S and HC rats than in C. High-density lipoprotein cholesterol (HDL-C) decreased in HC rats and total antioxidant substances (TAS) decreased in S and HC rats. There were positive correlations between BMI with carcass fat, BMI with LH and BMI and serum TG concentration. In conclusion, the BMI for male adult Wistar rats ranged between 0.45 and 0.68 g/cm(2). Obesity may be easily estimated from the BMI in rats. Alterations in BMI were associated with dyslipidemic profile and oxidative stress in serum of rats and BMI may predict these adverse consequences of the obesity in rats.
Keywords: obesity; body mass index; lipid profile; oxidative stress